INTERACTION METHOD BETWEEN WEBVIEW OBJECTS IN HYBRID JAVA APPLICATIONS - Denys Ratov; Oleh Zakhozhai (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2023)
The article deals with method of interaction between JavaScript objects of different web pages in hybrid java applications. To solve this problem, the WebView component is used, its functionality to provide an interface for JavaScript objects, as well as the SharedPreferences global settings class, with its ability to store data in local storage. The software implementation is considered and the results of the practical use of the developed method of interaction between JavaScript WebView objects in the form of a hybrid Java application embedded in the electronic university system – the Timetable SNU electronic timetable module are presented.